2019
DOI: 10.3390/cells8040375
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hedgehog Signaling in Breast Cancer: Pathogenesis and Therapeutics

Abstract: Breast cancer (BC) is the leading cause of cancer-related mortality in women, only followed by lung cancer. Given the importance of BC in public health, it is essential to identify biomarkers to predict prognosis, predetermine drug resistance and provide treatment guidelines that include personalized targeted therapies. The Hedgehog (Hh) signaling pathway plays an essential role in embryonic development, tissue regeneration, and stem cell renewal. Several lines of evidence endorse the important role of canonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 363 publications
(554 reference statements)
1
72
0
Order By: Relevance
“…Liu et al found that genetic ablation of SMO in stromal fibrosis could disrupt the paracrine SHH signaling with acinar-ductal metaplasia under a Kras G12D mouse model [90]. 4 -bis(2-pyridinylmethyl)-1,4-benzenedicarboxamide (MDB5) to inhibit pancreatic cancer [80]. Using a mouse model, Olive et al reported that SMO inhibitor enhances the vasculature within the tumor and facilitates the delivery of chemotherapy agents to pancreatic cancer [92].…”
Section: Shh In the Microenvironment Of Pancreatic Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…Liu et al found that genetic ablation of SMO in stromal fibrosis could disrupt the paracrine SHH signaling with acinar-ductal metaplasia under a Kras G12D mouse model [90]. 4 -bis(2-pyridinylmethyl)-1,4-benzenedicarboxamide (MDB5) to inhibit pancreatic cancer [80]. Using a mouse model, Olive et al reported that SMO inhibitor enhances the vasculature within the tumor and facilitates the delivery of chemotherapy agents to pancreatic cancer [92].…”
Section: Shh In the Microenvironment Of Pancreatic Cancermentioning
confidence: 99%
“…[114][115][116][117][118][119]. During embryonic development, the canonical SHH signaling pathway is inhibited in breast tissues [4,111], and SHH gene expression is affected temporally and spatially via genetic and epigenetic mechanisms [4,111]. In a mouse study, early mammary bud formation was found to require active repression of GLI1 by GLI3R [4].…”
Section: Colon Cancermentioning
confidence: 99%
See 3 more Smart Citations